Analysis of Interest in Learning Mathematics Using My Pals Book during Online Learning for Second-Grade Students at SDS Lazuardi Cordova GIS in the 2020/2021 Academic Year - Serlita Amalia; Febrianti Yuli Satriyani (Teknodika, 2022)
This study aims to (1) analyze the second-grade students' interest in learning mathematics at SDS Lazuardi Cordova GIS Jakarta, (2) reveal the factors influencing students' interest in learning, and (3) explain the efforts made by teachers to stabilize or develop students' interest in learning during online learning. The results revealed that (1) students' interest in learning mathematics using the My Pals book in online learning was in the high category, with a mean observation result of 85%. (2) The factors influencing students' interest in learning in mathematics included internal factors, namely factors from the students themselves, and external factors, i.e., motivation and attention from parents, facilities from schools, encouraging peers, and attention from the teacher. In addition, (3) the efforts made by teachers to stabilize or develop students' interest in learning mathematics were by providing interesting learning methods, such as discussion, lectures, slideshows, direct experiments, and doing projects, per the lower-grade students’ characteristics.